A study of single and two-phase flows in devices with narrow flow passages - Laskey, S. J. (Cranfield University, 2002)
In many industries, the depressurisation of gas-saturated solutionseis controlled to regulate bubble formation. Carbonated drink dispensers need to depressurise solutions with minimum bubble formation, whereas dissolved air flotation nozzles need to produce the maximum number of micro-bubbles. Four commercial carbonated drink dispensers were tested. The dispenser predicted to retain the most dissolved carbon dioxide at the outlet had a narrow annular gap of 0.1mm at the narrowest point. The pressure drop across this device varied linearly with water flow rate. When tested with two-phase air and water flow, the pressure drop decreased with increasing air flow at given water flowrates. This unusual behaviour was thought to be due to the narrow flow path. Carbon dioxide-saturated water tests supported these results as the pressure drop was found to be lower than the single-phase water tests. Thus under similar conditions, devices that create less turbulence would retain more dissolved gas. Flow in coils was investigated, as they have flow characteristics that were potentially suitable for carbonated drink dispensing. Compared to straight pipes, flow in coils remained laminar until higher Reynolds numbers. The friction factors were also higher in coils than straight pipes. Coils made from 0.0025m internal diameter polyurethane tubing were tested, with coil diameters of 0.029m, 0.079m and 0.139m and lengths of 2, 3, 3.7, 5 and 7m. A method of estimating the friction factors in coils by treating them as a series of 90° bends was proposed. The calculated results agreed with the present small tube experiments and with data from published literature for a range of tube diameters. At a given pressure drop, the shortest coil with the smallest coil diameter had the greatest dissolved gas concentration at the outlet and the highest flowrate. Furthermore, the concentration of dissolved gas at the coil outlet was greater than at the nozzle outlet.